Reallocating time to sleep, sedentary time or physical activity: associations with waist circumference and body mass index in breast cancer survivors. - Boyle, Terry; Vallance, J.; Buman, M.; Lynch, B. (American Association for Cancer Research Inc, 2016)
BACKGROUND: Moderate-to-vigorous intensity physical activity (MVPA) is inversely associated with waist circumference and body mass index (BMI) among breast cancer survivors. Limited research has focused on behaviours that account for larger portions of the day [sleep, sedentary time, and light-intensity physical activity (LPA)]. We investigated the interdependent associations of self-reported sleep, objectively-assessed prolonged and short bouts of sedentary time, total LPA and total MVPA with waist circumference and BMI. METHODS: A cross-sectional sample of breast cancer survivors (N=256, mean age=60 years; mean time since diagnosis=3 years) wore an Actigraph® GT3X+ accelerometer during waking hours for seven days. Participants completed the Pittsburgh Sleep Quality Index, and self-reported their waist circumference, height and weight. An isotemporal substitution approach was used in linear regression models to explore the associations of reallocating time to sleep, sedentary and active behaviours on waist circumference and BMI, after adjusting for potential confounders. RESULTS: Reallocating 30 minutes to MVPA was significantly associated with lower waist circumference when allocated from sleep (-2.50cm), prolonged sedentary time (-2.51cm) or LPA (-2.71cm). Reallocating 30 minutes of prolonged sedentary time to non-prolonged sedentary time was significantly associated with lower waist circumference ( 0.94cm). Similar results were observed for BMI. CONCLUSION: Reallocating 30 minutes to MVPA was associated with significantly lower waist circumference and BMI, as was reallocating 30 minutes of prolonged sedentary time to 30 minutes of non-prolonged sedentary time. IMPACT: Increasing MVPA levels and decreasing time spent in prolonged, unbroken sedentary bouts may be avenues for improving body composition in this population.